A bacteria-based bead for possible self-healing marine concrete applications. (15th July 2016) - Palin, D; Wiktor, V; Jonkers, H M
Abstract: This work presents a bacteria-based bead for potential self-healing concrete applications in low-temperature marine environments. The bead consisting of calcium alginate encapsulated bacterial spores and mineral precursor compounds was assessed for: oxygen consumption, swelling, and its ability to form a biocomposite in a simulative marine concrete crack solution (SMCCS) at 8 °C. After six days immersion in the SMCCS the bacteria-based beads formed a calcite crust on their surface and calcite inclusions in their network, resulting in a calcite–alginate biocomposite. Beads swelled by 300% to a maximum diameter of 3 mm, while theoretical calculations estimate that 0.112 g of the beads were able to produce ∼1 mm 3 of calcite after 14 days immersion; providing the bead with considerable crack healing potential. The bacteria-based bead shows great potential for the development of self-healing concrete in low-temperature marine environments, while the formation of a biocomposite healing material represents an exciting avenue for self-healing concrete research.